Microbial Communities of Peaty Permafrost Tundra Soils along the Gradient of Environmental Conditions and Anthropogenic Disturbance in Pechora River Delta in the Eastern European Arctic - Irina Kravchenko; Denis Grouzdev; Marina Sukhacheva; Tatyana Minayeva; Andrey Sirin (Diversity, 2023)
Microbial communities play crucial roles in the global carbon cycle, particularly in peatland and tundra ecosystems experiencing climate change. The latest IPCC assessments highlight the anthropogenic changes in the Arctic peatlands and their consequences due to global climate change. These disturbances could trigger permafrost degradation and intensification of the biogeochemical processes resulting in greenhouse gas formation. In this study, we describe the variation in diversity and composition of soil microbial communities from shallow peat tundra sites with different anthropogenic loads and applied restoration interventions in the landscape of remnant fragments of terraces in the Pechora River delta, the Russian Arctic, Nenets Autonomous Okrug. The molecular approaches, including quantitative real-time PCR and high-throughput Illumina sequencing of 16S RNA and ITS, were applied to examine the bacterial and fungal communities in the soil samples. Anthropogenic disturbance leads to a significant decrease in the representation of Acidobacteria and Verrucomicrobia, while the proportion and diversity of Proteobacteria increase. Fungal communities in undisturbed sites may be characterized as monodominant, and anthropogenic impact increases the fungal diversity. Only the verrucomicrobial methanotrophs Methyloacifiphilaceae were found in the undisturbed sites, but proteobacterial methanotrophs Methylobacterium-Methylorubrum, as well as different methylotrophs affiliated with Methylophilaceae, and Beijerinckiaceae (Methylorosula), were detected in disturbed sites.